2 µm high-power dissipative soliton resonance in a compact σ-shaped Tm-doped double-clad fiber laser. (3rd April 2018) - Du, Tuanjie; Li, Weiwei; Ruan, Qiujun; Wang, Kaijie; Chen, Nan; Luo, Zhengqian
Abstract: We report direct generation of a high-power, large-energy dissipative soliton resonance (DSR) in a 2 µm Tm-doped double-clad fiber laser. A compact σ-shaped cavity is formed by a fiber Bragg grating and a 10/90 fiber loop mirror (FLM). The 10/90 FLM is not only used as an output mirror, but also acts as a nonlinear optical loop mirror for initiating mode locking. The mode-locked laser can deliver high-power, nanosecond DSR pulses at 2005.9 nm. We further perform a comparison study of the effect of the FLM's loop length on the mode-locking threshold, peak power, pulse energy, and optical spectrum of the DSR pulses. We achieve a maximum average output power as high as 1.4 W, a maximum pulse energy of 353 nJ, and a maximum peak power of 84 W. This is, to the best of our knowledge, the highest power for 2 µm DSR pulses obtained in a mode-locked fiber laser.